Supplier selection for steelmaking company by using combined Grey-MARCOS methods - Ibrahim Badi (Decision Making: Applications in Management and Engineering, 2020)
Abstract. The process of selecting the right suppliers should be seen as more than simply scanning a set of available price lists and comparing them, but rather as including a wide range of different criteria, whether qualitative or quantitative. In contemporary supply chain management, potential supplier performance is evaluated on the basis of multiple criteria rather than considering cost as the main criterion in decision-making.  This makes the process of selecting the best supplier from a group of suppliers a complex and difficult process, due to the multiplicity of criteria that must be taken into account in the evaluation process. The aim of this study is to implement a hybrid Grey theory-MARCOS methods for decision-making regarding the selection of suppliers in the Libyan Iron and Steel Company (LISCO) to help it compete. This hybrid model is divided into two phases: the first consists of determining the weights of the criteria that contribute to decision-making, which has been done using the Grey theory, and the second phase consists of selecting the best supplier from among  the six suppliers, which has been completed using  the MARCOS model. For the purpose of measuring the effectiveness of the model, it has been compared to three other methods, CODAS, TOPSIS, and VIKOR. The results showed that the proposed method was effectively able to select the best supplier among the six alternative suppliers.